Frequency, size and location of apical and lateral foramina in anterior permanent teeth - Abdullah, D.A; Kanagasingam, S; Luke, D.A (Universiti Kebangsaan Malaysia, 2013)
The aim of the study was to determine the frequency, size and location of apical and lateral foramina on anterior teeth. A total of 100 anterior teeth consisting of maxillary and mandibular incisors and canines were fixed in 10% formalin. Periodontal tissue remnants were mechanically removed and teeth were stained in 2% aqueous silver nitrate. The teeth were dried and examined using a Leica MZ 7.5 zoom stereomicroscope. The size of apical and lateral foramina and their distance from the anatomical apex of the tooth were measured directly using a calibrated eyepiece scale. Accessory foramina more than 1.8 mm from the apex were regarded as lateral foramina. Eighteen percent of teeth possessed more than one apical foramen. Seven teeth (three maxillary centrals, three maxillary canines, one mandibular lateral) had 11 lateral foramina each. The mean diameter of the lateral foramina was 0.14 mm (SD = 0.08) and their mean distance from the apex was 4.49 mm (SD = 2.63, range 1.9-10.5 mm). Multiple foramina were most common on maxillary canines and least common on maxillary laterals. The mean diameter of apical foramina for all teeth possessing a single foramen was 0.35 mm (SD = 0.10) and the mean apical foramen diameter for all teeth with multiple apical foramina was 0.22 mm (SD = 0.08). Most anterior teeth possess one apical foramen and no lateral foramina; about 20% possessed more than one apical foramen and about 10% possessed one or more lateral foramina. These findings should be considered when root-treating anterior teeth.